2008
DOI: 10.1111/j.1467-7652.2008.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean WRKY‐type transcription factor genes,GmWRKY13, GmWRKY21, andGmWRKY54, confer differential tolerance to abiotic stresses in transgenicArabidopsisplants

Abstract: Summary WRKY‐type transcription factors have multiple roles in the plant defence response and developmental processes. Their roles in the abiotic stress response remain obscure. In this study, 64 GmWRKY genes from soybean were identified, and were found to be differentially expressed under abiotic stresses. Nine GmWRKY proteins were tested for their transcription activation in the yeast assay system, and five showed such ability. In a DNA‐binding assay, three proteins (GmWRKY13, GmWRKY27 and GmWRKY54) with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
423
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(449 citation statements)
references
References 66 publications
(77 reference statements)
23
423
2
1
Order By: Relevance
“…These encouraging crop plant-based results are supplemented by others in the model plant Arabidopsis and further evidence came from altered plant responses to different abiotic stresses following the overexpression of three stress-inducible soybean wRKY genes in Arabidopsis. Zhou et al (2008) revealed enhanced cold tolerance in comparison to wild type when GmWRKY21 was overexpressed. In comparison, GmWRKY54-overexpressing plants were shown to be more salt and drought tolerant and GmWRKY13 overexpression resulted in increased sensitivity to salt and mannitol stresses (Zhou et al 2008).…”
Section: Abiotic Stress and Wrky Transcription Factors: Altered Exprementioning
confidence: 99%
See 1 more Smart Citation
“…These encouraging crop plant-based results are supplemented by others in the model plant Arabidopsis and further evidence came from altered plant responses to different abiotic stresses following the overexpression of three stress-inducible soybean wRKY genes in Arabidopsis. Zhou et al (2008) revealed enhanced cold tolerance in comparison to wild type when GmWRKY21 was overexpressed. In comparison, GmWRKY54-overexpressing plants were shown to be more salt and drought tolerant and GmWRKY13 overexpression resulted in increased sensitivity to salt and mannitol stresses (Zhou et al 2008).…”
Section: Abiotic Stress and Wrky Transcription Factors: Altered Exprementioning
confidence: 99%
“…Zhou et al (2008) revealed enhanced cold tolerance in comparison to wild type when GmWRKY21 was overexpressed. In comparison, GmWRKY54-overexpressing plants were shown to be more salt and drought tolerant and GmWRKY13 overexpression resulted in increased sensitivity to salt and mannitol stresses (Zhou et al 2008).…”
Section: Abiotic Stress and Wrky Transcription Factors: Altered Exprementioning
confidence: 99%
“…Rushton et al 2010;Chen et al 2012;Tripathi et al 2014;Schluttenhofer and Yuan 2015). Overexpression of soybean GmWRKY13 in Arabidopsis conferred higher sensitivity to salinity and osmotic stress in the transgenic plants (Zhou et al 2008). On the other hand, the expression of the barley HvWRKY38 in Paspalum notatum Flugge increased the drought tolerance of the transgenic plants (Xiong et al 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…An increase in the GmbZIP62 (Liao et al 2008) was also observed in the transgenic plants. The RNA level of the abiotic stress responsive genes, ethylene response factor gene GmERF3 (Zhang et al 2009) and WRKY-type transcription factor gene GmWRKY54 (Zhou et al 2008) barely increased. In case of the osmotin-like protein b isoform gene GmOLPb (Tachi et al 2009) and plant-homeo-domain gene GmPHD2 ), their expressions enhanced significantly in the transgenic plant.…”
Section: Expression Analysis Of Abiotic Stress Responsive Genes In Trmentioning
confidence: 99%